Analisis Buku Teks Bahasa Indonesia Kelas X SMAN 5 Pekanbaru Karangan Kementrian Pendidikan dan Kebudayaan - Ijah, Nurul (J-LELC: Journal of Language Education, Linguistics, and Culture, 2022)
Education is an important factor in producing the quality of human resources. Textbooks are used by teachers to help the teaching and learning process. The textbook itself must be interesting in terms of content, language, and others so that students who read it are more enthusiastic about learning it. This research is entitled "Analysis of Textbooks Indonesian Class X SMAN 5 Pekanbaru Published by the Ministry of Education and Culture". Objective : The research is to describe, analyze and interpret textbooks Indonesian are worthy (meet the criteria) for use by students of SMAN 5 Pekanbaru in terms of material content, presentation, graphs and language. The research approach is descriptive. The data collection technique is to analyze and interpret class X Indonesian textbooks published by the Ministry of Education and Culture by adhering to the muslich theory. Results : analysis of the ministry of education and culture books by adhering to the muslich theory can be stated that the books of class X students are compiled, published and distributed by the ministry of education and culture of quality